2003
DOI: 10.1016/s0168-6496(03)00131-4
|View full text |Cite
|
Sign up to set email alerts
|

Baltic Sea cyanobacterial bloom contains denitrification and nitrification genes, but has negligible denitrification activity

Abstract: A cyanobacterial bloom in the Gulf of Finland, Baltic Sea, was sampled throughout the development and senescence of aggregates in August 1999. While conditions inside the aggregates were favourable for denitrification (rich in nitrogen and carbon, with anoxic microzones), essentially none was detected by a sensitive isotope pairing method. Polymerase chain reaction-based methods, targeting functional genes encoding the key enzymes of denitrification and nitrification processes (nirS, nirK, amoA), revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 66 publications
2
31
1
Order By: Relevance
“…In the present work, despite the prevalence of the nirS gene in biofilms amended with P alone, denitrification was not stimulated, suggesting that another factor may be limiting for the activity of nirS-harboring denitrifiers. Similarly, it was recently reported that Baltic Sea cyanobacteria contained denitrification genes but that, despite optimal environmental conditions and genetic potential, had negligible denitrification activity (60). In the present study, the addition of CNP resulted in significant increases in cyanobacterial biomass (P Ͻ 0.05) in both years, especially in the presence of hexadecane.…”
Section: Discussionsupporting
confidence: 81%
“…In the present work, despite the prevalence of the nirS gene in biofilms amended with P alone, denitrification was not stimulated, suggesting that another factor may be limiting for the activity of nirS-harboring denitrifiers. Similarly, it was recently reported that Baltic Sea cyanobacteria contained denitrification genes but that, despite optimal environmental conditions and genetic potential, had negligible denitrification activity (60). In the present study, the addition of CNP resulted in significant increases in cyanobacterial biomass (P Ͻ 0.05) in both years, especially in the presence of hexadecane.…”
Section: Discussionsupporting
confidence: 81%
“…Besides sequences from taxonomically described isolates, the overall tree also included all nirS sequences of unknown affiliation retrieved from other marine systems that were available in the database. These sequences were retrieved from the water column of the eastern South Pacific (ESP, Castro-Gonzalés et al, 2005), the Arabian Sea (ASW, Jayakumar et al, 2004), and the Northern Baltic Sea (CBBS, Tuomainen et al, 2003) and sediments of the Pacific Northwest (PNW, Braker et al, 2000) and the eastern tropical North Pacific (ETNP, Liu et al, 2003). Phylogenetic analysis revealed seven major clusters of marine nirS sequences (marine Clusters I-VII).…”
Section: Phylogenetic Affiliation Of Nirs Sequences From Marine Habitatsmentioning
confidence: 99%
“…Denitrification rates have been measured in Baltic sediments (e.g. central Gulf of Finland) using the isotope pairing method (Tuominen et al, 1998). This study revealed that the bulk of denitrification was coupled to NO − 3 production by nitrification.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the initial pool of NO 3 -in the incubations was transformed to NH 4 + (via dissimilatory nitrate reduction to ammonia, DNRA) or gaseous compounds of nitrogen such as N 2 , NO and N 2 O (denitrification sensu strictu) (Zumft 1997) is not clear at this stage. Cyanobacterial aggregates in the Baltic Sea were found to contain denitrification genes, but denitrification activity was found to be negligible (Tuomainen et al 2003). The results shown in Fig.…”
Section: Bacteria Potentially Involved In Iron Reductionmentioning
confidence: 84%
“…Even though very few investigations have been specifically directed towards anaerobic bacteria, methanogenic, NO 3 --and SO 4 2 --reducing bacteria have all been detected in different natural and artificial aggregates (Bianchi et al 1992, Bockelmann et al 2000, Grossart & Ploug 2000, Tuomainen et al 2003. However, dissimilatory iron reduction, which has been well described in many environments (Lloyd 2003, Lovley et al 2004, has never been investigated in marine aggregates.…”
Section: Introductionmentioning
confidence: 99%